METODOLOGI KITAB AL-ISRÂ’ÎLIYYAT WA AL-MAUDHÛ’ÂT FÎ KUTUB AL-TAFSÎR KARYA SHEIKH ABU SYAHBAH: SATU ANALISIS - Zahidah Zainal Abidin (Jurnal Ilmiah Ilmu Ushuluddin, 2017)
Kitab al-Isrâ’îliyyat wa al-Maudhûcât fi Kutub al-Tafsîr is the great work of Sheikh Abu Shahbah which tells the stories of Israiliyyat that exist in the Qur'an and Hadith. This book is considered as an important effort to know the elements of dakhil in the commentaries. This book has been raised as the main and best reference in the discussion of Israiliyyat in the Fakulti Pengajian Islam, Universiti al-Azhar. This study analyzes the methodology used by Sheikh Abu Shahbah in this book. It also briefly discusses the background of Abu Shahbah as a respected muhaddith. This study is a qualitative one and focuses to analyze Abu Shahbah’s work, al-Isrâ’îliyyat wa al-Maudhûcât fi Kutub al-Tafsîr. The results of this study do have the features and strengths that are mutually studied and utilized. The form of argumentation in this work encompasses the Qur'an, the hadith of muktabar, the ijtihad of the scholars' salaf, his views, and some of the latest scientific theories of natural phenomena related to Israiliyat.